Evaluasi awal produksi getah uji keturunan pinus merkusii jungh et de vriese di KPH Banyumas Barat - Imam Muslimin (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2013)
The research aimed to assess genetic variations, estimated heritability and genetic gain in resin yield of P. merkusii. The study was conducted on a half-sib progeny test of 4-year-old P. merkusii resin yield plantation at compartment 37C RPH Lumbir BPKH Samudra KPH Banyumas Barat, using incompletely-block-row-column design by sub-line system (sub-line SSO Jember 1, SSO Sumedang 1, Sulawesi 1, Sulawesi 2 and Jatim 2). Variables measured were average of resin yield from two drillings on the right and left trunk using 10 mm drill bit at 50 cm height from the ground. Genetic variation for resin yield between family was significant different except for sub-line SSO Jember 1. Estimated component variances of family for the sub-line SSO Sumedang 1, Sulawesi 1, Sulawesi 2 dan Jatim 2 were 8.92%; 9.87%; 7.53% and 6.74%, respectively. Individual heritability values were 0.39; 0.42; 0.36; 0.29 and family heritability were 0.59; 0.49; 0.50; 0.48 respectively for the sub-line SSO Sumedang 1, Sulawesi 1, Sulawesi 2 and Jatim 2. Expected genetic gains in resin yield were 14.5%, 10.5% and 6.6% using intensity of selection of 10%, 25% and 50%, respectively. Sub-line Sulawesi 1 had the highest estimated genetic gain and sub-line Jatim 2 was the lowest